Efficacy of nutrition counselling in young people with diabetes - La Loggia, A.; Bivona, L. (Acta Biomedica Atenei Parmensis, 2011)
Aim: The aim of this study is to investigate if a non-prescriptive diet plan in young children with type 1 diabetes mellitus is unfavourable in comparison with classic prescriptive diet plan, paying particular attention to glycemic control, lipid profile and body mass index. Methods: We carried out a longitudinal and 8-year retrospective study based on a well-defined cohort of children aged < 18 years with type 1 diabetes followed-up every three months from our Unit beginning from 1999 to 2007. The study included a total of 49 patients with type 1 diabetes aged 16–19 years, the mean duration of diabetes was 13 ± 4 years. During the study all the patients continued to receive flexible multiple daily injection insulin therapy according to basal-bolus plan. In order to investigate the lipid profile we collected total cholesterol, LDL, HDL and triglyceride levels once a year and to asses the metabolic control in diabetic patients, blood samples were collected for assay of HbA1c every three months all years during the study. Results: No abnormalities about lipid profile were observed during the analysed years. LDL, HDL, total cholesterol and triglyceride values were normal and  their trend was uniform and lower than the normal range of general people. Conclusions: These outcomes showed no differences between diabetics and normal people at risk to develop metabolic alterations. Non-prescriptive diet plan in children with insulin dependent diabetes mellitus is not unfavourable in comparison with classic prescriptive diet-plan, in particular with regard tos the metabolic control which reflect the international data of reference.